Hemopericardium with Subdural Hemorrhage: A Rare Case - Bhoi, S B; Shinde, D K; Chandekar, K S; Mahajan, N P; Tumram , N K (Journal of Indian Academy of Forensic Medicine, 2014)
The incidence of simultaneous occurrence of intracranial hemorrhage and hemopericardium due to the rupture of a dissecting aneurysm is very rare. We describe an autopsy case of a 52-year-old male with hypertension who died suddenly. He had been treated for hypertension. During post-mortem examination we found pericardial cavity filled with blood and blood clots. This hemopericardium was due to rupture of dissecting aortic aneurysm. Ascending aorta shows ruptured dissecting aortic aneurysm [De Bakey type 2]. Intramural hematoma present in the wall of ascending aorta. Histologically, the wall of the aneurysm revealed cystic medial necrosis, which appears to idiopathic in nature. There was also evidence of subdural hemorrhage. After analyzing the findings the opinion as to the cause of death was “Hemopericardium due to rupture of dissecting aortic aneurysm along with intracranial bleeding.” As per our view in present case the subdural hemorrhage was occurred after the rupture of dissecting aortic aneurysm when the venous pressure increases, leading to the rupture of bridging vein in subdural space.